PERJALANAN JIWA KE “KAMPUNG LELUHUR” KONSEP KEMATIAN MENURUT KEPERCAYAAN ASLI MASYARAKAT SUMBA (MARAPU) DAN PERJUMPAANNYA DENGAN AJARAN KATOLIK (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
This study answers a phenomenon of double funeralrite that often occurs among the Catholics who converted from Marapu, the ethnic religion of the people of Sumba. Double funeralrite is the practice of funeral ceremonies consisting of official liturgy of the Catholic Church and spontaneously followed by a number of Marapu rites. Such a practice indicates a dualism of belief, in the sense that people have embraced the Catholic faith but are still attached to the elements of their old beliefs. In this study the author investigates in depth both the funeral rites according to Marapu and the double practice phenomenon in funeral ceremonies of Catholics who converted from Marapu. The main purpose of this research is to find parallels and intersections between Catholic’s concept of life after death and that of Marapu’s. Discussion and analysis of the data prioritizes the meaning behind each verbal and non-verbal expression. The meaning of prayers, rituals and symbols used in funeral according to Marapu reveals universal values ??that parallel to the values ??contained in Catholic teaching. According to Marapu belief, death is the return of the soul towards “ancestral village”, which is the final resting place of souls after death. This return is believed to be a long journey before arriving at the ancestral village. Prayers and ceremonies carried out by humans aim to help the soul to enter the ancestral village. This concept parallels to the Catholic understanding of soul purification after death before entering the eternal happiness in Heaven. Such parallels allow a construction of the encounter between Catholic teachings and Marapu ones about life after death.
Keywords: Hidup setelah mati; Upacara; Marapu; Katolik; Perjumpaan